Evaluating Ammonia Toxicity and Growth Kinetics of Four Different Microalgae Species - Metin, Umut; Altinbas, Mahmut (MDPI, 2024)
Although wastewater with high ammonia concentration is an ideal alternative environment for microalgae cultivation, high ammonia concentrations are toxic to microalgae and inhibit microalgae growth. In this study, the ammonia responses of four widely used microalgae species were investigated. Chlorella vulgaris, Chlorella minutissima, Chlamydomonas reinhardtii and Arthrospira platensis were grown in batch reactors maintained at seven different NH4Cl concentrations at a constant pH of 8. Growth and nitrogen removal kinetics were monitored. IC50 values for the mentioned species were found as 34.82 mg-FA/L, 30.17 mg-FA/L, 27.2 mg-FA/L and 44.44 mg-FA/L, respectively, while specific growth rates for different ammonia concentrations ranged between 0.148 and 1.271 d-1. C. vulgaris demonstrated the highest biomass growth under an ammonia concentration of 1700.95 mg/L. The highest removal of nitrogen was observed for A. platensis with an efficiency of 99.1%. The results showed that all tested species could grow without inhibition in ammonia levels comparable to those found in municipal wastewater. Furthermore, it has been concluded that species C. vulgaris and A. platensis can tolerate high ammonia levels similar to those found in high strength wastewaters.
Keywords: microalgae; ammonia toxicity; nitrogen; wastewater; WASTE-WATER; CHLORELLA-MINUTISSIMA; SPIRULINA-PLATENSIS; NUTRIENT REMOVAL; CHLAMYDOMONAS-REINHARDTII; ARTHROSPIRA-PLATENSIS; NITROGEN REMOVAL; LIPID PRODUCTION; CULTIVATION; BIOMASS; Microbiology